2022
DOI: 10.1021/acs.analchem.2c01164
|View full text |Cite
|
Sign up to set email alerts
|

Highly Facile Strategy for Detecting D2O in H2O by Porphyrin-Based Luminescent Probes

Abstract: Owing to their almost similarities in size, shape, and chemical reactivity, effectively distinguishing deuteroxide (D 2 O) in water (H 2 O) remains an ongoing challenge, and the examples of a D 2 O probe are still quite scarce.Herein, since H 2 O can decrease the lifetime of a singlet oxygen as a vital intermediate and an H/D exchange in the luminescence process of porphyrins, we systematically investigated the enhanced ultraviolet−visible (UV−vis), photoluminescence (PL), and electrochemiluminescence (ECL) of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Considering this, recently optical sensors have become the easiest and most efficient technique to track the presence of humidity or moisture in the field of food processing, biomedical applications, chemical production, and storage industry . In the same line, the probability of water contamination is very high in the case of D 2 O as it has a high tendency to absorb moisture due to its hygroscopic nature. , For detection of the H 2 O concentration in D 2 O, the following methods have been explored previously: NMR, atomic absorption spectroscopy, and infrared laser spectroscopy . Unfortunately, these approaches have several drawbacks, including the need for specialized instruments, intricate procedures, and lengthy processes, which make them unsuitable for real-time analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Considering this, recently optical sensors have become the easiest and most efficient technique to track the presence of humidity or moisture in the field of food processing, biomedical applications, chemical production, and storage industry . In the same line, the probability of water contamination is very high in the case of D 2 O as it has a high tendency to absorb moisture due to its hygroscopic nature. , For detection of the H 2 O concentration in D 2 O, the following methods have been explored previously: NMR, atomic absorption spectroscopy, and infrared laser spectroscopy . Unfortunately, these approaches have several drawbacks, including the need for specialized instruments, intricate procedures, and lengthy processes, which make them unsuitable for real-time analysis.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the D 2 O content was 19.57 nm. Compared with the laser-based method widely used in actual sample detection, it showed more accurate quantification. , Such an eminent result demonstrated that the indene-based ECL method could serve as a reliable ECL sensor for D 2 O detection in practical application. Meanwhile, we have also studied the detection mechanism. As depicted in Figures S11 and S12, Supporting Information, the 1 H NMR and MS spectra of indene were measured after D 2 O detection, and the results clearly showed the hydrogen/deuterium exchange at the 1-position of indene.…”
Section: Resultsmentioning
confidence: 94%
“…•− returned to SO 4 2− (3). Last, Zn 2+ -GCA* radiated energy in the form of light as it went back to the ground state (4).…”
Section: ■ Results and Discussionmentioning
confidence: 99%